Cognitively Based Compassion Training for HIV Immune Nonresponders—An Attention-Placebo Randomized Controlled Trial. (1st March 2022) - Titanji, Boghuma K.; Tejani, Mehul; Farber, Eugene W.; Mehta, C. Christina; Pace, Thaddeus W.; Meagley, Kathryn; Gavegnano, Christina; Harrison, Timothy; Kokubun, Caroline W.; Negi, Satya Dev; Schinazi, Raymond F.; Marconi, Vincent C.
Abstract : Objective: Chronic inflammation is associated with increased morbidity and mortality for people with HIV (PWH). Psychological stress is an important contributor to this chronic inflammation. We hypothesized that a cognitively based compassion training (CBCT) approach could reduce inflammation and psychological stress in immune nonresponder PWH. Design: An attention-placebo randomized controlled trial design to evaluate the acceptability of CBCT among PWH and its effects on key aspects of stress and immune function compared with an active-attention control group (NCT02395289). Methods: This study was conducted at an HIV clinic in Atlanta, Georgia. Eligible individuals determined by (1) adherence to antiretroviral therapy for at least a year, (2) virologic suppression; and (3) stable CD4 + T-cell counts <350 cells/μL were randomized in a 2:1 ratio to either CBCT or control in 2 study periods: April–May, 2016, and September–December, 2016. Psychological measures and inflammatory biomarkers associated with HIV disease progression (IL-1β, TNF-α, sCD14, IL-6, and IL-10) were obtained for all study participants at baseline and at the time of study completion. Results: We found a significant association between CBCT practice time engagement and fold reduction in IL-6 and TNF-α levels. There was no association between CBCT practice time and other biomarkers markers assessed (IL-1β, sCD14, and IL-10). These changes were coincident with significant increases in self-reported psychological well-being and HIV disease acceptance and in benefits for CBCT participants. We also observed fewer instances of virologic failure for those in the CBCT arm compared with controls. Conclusions: CBCT is a novel and feasible nonmedication-based intervention that could reduce inflammation and psychological stress in PWH. Abstract : Supplemental Digital Content is Available in the Text.